P214 Gastro-Oesophageal Reflux Symptoms During COPD Exacerbations. (19th November 2012) - Patel, ARC; Kowlessar, BS; Donaldson, GC; Mackay, AJ; Singh, R; Brill, S; Wedzicha, JA; Hurst, JR
Abstract : Introduction: Gastro-oesophageal reflux disease (GORD) has been associated with increased COPD exacerbation frequency (Terada et al, Thorax 2008) and was independently associated with the frequent exacerbator phenotype in the ECLIPSE study (Hurst et al, NEJM 2010). We aimed to quantify any changes in GORD symptoms during COPD exacerbations. Methods: Outpatients from the London COPD cohort completed the Frequency Scale for the Symptoms of Gastro-oesophageal reflux (FSSG) and Hull Airway Reflux Questionnaire (HARQ) during stable-state clinic visits and at exacerbation, within a week of symptom-onset, and prior to systemic therapy. FSSG and HARQ scores range from 0–48 and 0–70 respectively, with significant reflux thought to be associated with scores of ≥8 and ≥13 respectively. Exacerbations were defined using our usual symptomatic criteria from daily diary cards (Seemungal et al, AJRCCM 1998). Results: 42 COPD patients had a mean±SD age of 72.7±8.7 years, 64% male, 17% current smokers, median(IQR) 46 (19.71) pack years, mean±SD stable FEV1 1.22±0.64L and 50.7±21.5%predicted, BMI 27.7±7.4kg/m2. 13 (31%) patients had a diagnosis of GORD, of whom 12 (92%) were taking regular acid suppression therapy. There was a median (IQR) interval of 141(80, 233) days between the stable and exacerbation visits. Although median (IQR) FSSG and HARQ scores were higher at exacerbation compared to the stable state, this was not statistically significant due to high variability (6.5 (4.0, 13.0) vs 5.0 (1.5, 11.5), p=0.247 and 15.5 (9.0, 23) vs 18.5 (11.5, 24.5), p=0.096 respectively). 16/42 (38%) patients had a high FSSG score (≥8) in the stable state compared with 20/42 (48%) at exacerbation (p=0.378). 10/42 (24%) changed from a low stable FSSG to a high score at exacerbation. 27/42 (64%) patients had a high HARQ score (≥13) in the stable state compared with 30/42 (71%) at exacerbation (p=0.483). 7/42 (17%) changed from a low stable HARQ to a high score at exacerbation. Conclusions: GORD symptom scores are not significantly higher during acute COPD exacerbations. Due to high variability, approximately one fifth of COPD patients had a low GORD symptom score when stable and high scores at exacerbation implicating worsening reflux in some exacerbations. Further work is required to understand the potential mechanisms.